The Effect of Work Motivation and Job Satisfaction on the Performance of State Civil Apparatus with Work Discipline as an Intervening Variable at the Office of the Airport Authority Region X Papua, Merauke - Wahyudi, Yudi; Henry S, Jack; Nurhayati, Mafizatun (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study focuses on discussing the effect of work motivation, job satisfaction on the performance of state civil apparatus with work discipline as an intervening variable at the Office of the Airport Authority Region X Merauke, Papua. The type of research used is quantitative with a causal study design. Data collection through questionnaires and analyzed using multivariate-Structural Equation Model analysis. The results of this study see a significant influence between motivation and job satisfaction on the performance and work discipline of the State Civil Apparatus. However, when testing discipline as a mediating variable between motivation, satisfaction and performance, it was found that the relationship was not significant. As recommendations, implement employee development programs focused on increasing motivation and job satisfaction, provide regular training and workshops to improve work discipline and performance, and conduct periodic job satisfaction surveys to identify areas that require improvement. Recommendations for employees, actively participate in development programs offered by the office, provide constructive feedback to management, and take initiative in improving work discipline.